Tspan8 and Tspan8/CD151 knockout mice unravel the contribution of tumor and host exosomes to tumor progression - Zhao, Kun; Wang, Zhe; Hackert, Thilo; Pitzer, Claudia; Zöller, Margot (Journal of experimental & clinical cancer research, 2018)
The tetraspanins Tspan8 and CD151 promote metastasis, exosomes (Exo) being suggested to be important in the crosstalk between tumor and host. The contribution of Tspan8 and CD151 to host versus tumor-derived exosome (TEX) activities being not defined, we approached the questions using 3-methylcholanthrene-induced (MCA) tumors from wt, Tspan8ko, CD151ko and Tspan8/CD151 (db)ko mice, implanted into tetraspanin-competent and deficient hosts.